P14.122 Integrin α5 is a poor prognostic factor in patients with glioblastoma treated by the Stupp protocol. (6th September 2019) - Etienne-Selloum, N; Prades, J; Bello Roufai, D; El Azumi, F; Boone, M; Sevestre, H; Trudel, S; Coutte, A; Desenclos, C; Constans, J; Chauffert, B; Dontenwill, M
Abstract: BACKGROUND: Integrin α5β1 was suggested to be involved in glioblastoma (GBM) aggressiveness through preclinical studies and genomic analysis of several cohorts of patients. However, protein expression data are still missing to confirm this hypothesis. Our aim was to investigate the prognostic value of integrin α5 protein expression level in GBM. MATERIAL AND METHODS: We retrospectively determined the protein expression level of integrin α5 using immunochemistry in tumors from patients treated in 6 French centers. Paraffin sections of GBM were labeled by immunofluorescence and analyzed by confocal microscopy. The corresponding clinical and survival data have been identified and analyzed. The primary end-point was overall survival (OS). RESULTS: Out of 297 patients newly diagnosed with GBM between 2006 and 2013, 152 met the inclusion criteria (scheduled for initial treatment with the Stupp protocol, age > 18 years) and 95 tumor samples were suitable for immunohistochemical analysis. The median age is 58 years, (64 men, 34 women). Most of patients received macroscopic (43%) or partial (36%) surgery. In univariate analysis using the Log Rank test, high integrin α5 expression level was associated with poor prognosis (PFS: hazard ratio (HR) = 1, 696, p=0, 0355; OS: HR=1, 598, p = 0, 0508). Corresponding median OS were 15, 6 versus 19, 2 months. Similarly, OS was significantly reduced with age (> 60 years), lower resection degree, higher RPA (recursive partitioning analysis) score and non-methylated MGMT (O-6-methylguanine-DNA methyltransferase) promoter. In the subgroup of patients who received the full initial protocol (temozolomide treatment together with radiotherapy and later as adjuvant treatment; n=58) mean OS was strongly reduced when integrin α5 expression level was high (15, 6 versus 22, 8 months, p=0, 0162) suggesting an impact of integrin signaling on temozolomide response in GBM. CONCLUSION: Our study validates for the first time that the high protein level expression of α5 integrin is associated with poor prognosis in GBM. It also confirms its potential as a therapeutic target and its likely role in resistance to temozolomide as previously shown in preclinical study.